APPLICATION OF THE MONTE CARLO METHOD IN THE SOLUTION OF RADIATION HEAT TRANSFER IN PARTICIPATING MEDIA - Maurente, A.; Bayer, P. O.; França, F. H. R. (Revista de Engenharia Térmica, 2007)
The temperatures of the gases produced in combustion processes are very high so thermal radiation constitutes an important heat transfer mechanism in industrial furnaces. Most furnaces can be modeled as gray enclosures containing non-gray gases. The radiation heat transfer can be obtained with the aid of the weighted-sum-of-gray-gases model, determining the zonal exchange areas for each of the gray gases considered in the sum. For some enclosures with simple geometries, there are correlations to obtain the direct exchange-areas which can be used to determine the total exchange areas. However, for enclosures with complex geometries, determining the direct exchange areas can become a difficult task. In this case, the use of the Monte Carlo method is advantageous, for it allows one to approach geometric complexities without additional complications. Therefore, the method was applied to compute total exchange areas in enclosures containing participating media. Two cases were considered: cylindrical enclosures and enclosures that have generic geometries formed from cube combinations. The results presented a good agreement with solutions available in the literature.